Kajian Literatur: Fenomena Viral Brand dan Dampak Pada Pembelian Mixue - Dabitha Wise Maliha; Meci Nilam Sari; Azmen Kahar; Rika Septrizarty; Sharnuke Asrilsyak (Departement of Mathematics Education, 2023)
Since 2020, Mixue has started to expand in Indonesia and experienced rapid development by opening 317 outlets by the end of March 2022. The massive opening of Mixue outlets cannot be separated from the viral phenomenon among netizens. This article aims to analyze the literature review related to the virality of the Mixue brand and its impact on product purchases. There are 5 scientific works have been analyzed and the results show that viral marketing has a positive and significant influence on consumer interest and purchasing decisions. Furthermore, turbo marketing can also positively and significantly influence on consumer purchasing decisions. Finally, the existence of brand image and brand awareness can also have a positive and significant influence on consumer purchasing decisions.